(untitled) (Journal of Enam Medical College, 2018)
Background: Pelvic inflammatory disease (PID) is a major health problem for adult female. Women presented with pelvic inflammatory diseases give different per-vaginal findings. So we designed this study to assess the per-vaginal findings among the women presented with pelvic inflammatory diseases. Objective: The purpose of the present study was to measure the pervaginal findings among the women with PID. Materials and Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at Dhaka Medical College & Hospital, Dhaka during January to June 2007. Women in the age group of 15−45 years presented with lower abdominal pain, tenderness, per-vaginal discharge and cervical motion tenderness were included in this study. After taking verbal consent from the patients, a pre-designed data collection sheet was filled in after per-vaginal examination. Results: The study was done on 50 cases, of which 20% patients had 1st degree perineal tear, 6% had utero-vaginal prolapse and 24% had foul-smelling vaginal discharge. Majority (90%) patients had healthy vagina. Ninety percent patients had anteverted uterus; and uterus was mobile in 60% cases. Cervical motion tenderness was present in 44% cases, tenderness of fornix was found in 34% cases and thickening of fornix was found in 22%. Conclusion: In this study first degree perineal tear, foul smelling vaginal discharge and cervical motion tenderness are the commonest findings among the women presented with pelvic inflammatory diseases. J Enam Med Col 2018; 8(2): 90-93